2017
DOI: 10.1155/2017/8321325
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Solubility of Diclofenac β‐Cyclodextrin in Combination with Local Anaesthetics for Mesotherapy Applications

Abstract: Because of low injection volume, the recently marketed injectable solution of diclofenac in complex with β-cyclodextrin (Akis®, IBSA Farmaceutici Italia) is an ideal candidate for mesotherapy applications. In this study, we investigated the solubility of Akis, 25 and 50 mg/kg, in combination with various local anaesthetics (lidocaine, mepivacaine, bupivacaine, levobupivacaine, and ropivacaine) at different concentrations in aqueous vehicles (normal saline, sterile water, or bicarbonate). Final injection mixtur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Local anaesthetic and NSAID admixtures may precipitate, however, and more studies of compatibility are required. Diclofenac solution and bupivacaine, levobupivacaine or ropivacaine admixtures are incompatible as precipitation occurs even in the presence of sodium bicarbonate [115]. Lidocaine and diclofenac are only compatible in an alkalinised solution [115] but mixing is not recommended in the product licence.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Local anaesthetic and NSAID admixtures may precipitate, however, and more studies of compatibility are required. Diclofenac solution and bupivacaine, levobupivacaine or ropivacaine admixtures are incompatible as precipitation occurs even in the presence of sodium bicarbonate [115]. Lidocaine and diclofenac are only compatible in an alkalinised solution [115] but mixing is not recommended in the product licence.…”
Section: Resultsmentioning
confidence: 99%
“…Diclofenac solution and bupivacaine, levobupivacaine or ropivacaine admixtures are incompatible as precipitation occurs even in the presence of sodium bicarbonate [115]. Lidocaine and diclofenac are only compatible in an alkalinised solution [115] but mixing is not recommended in the product licence. Intravenous diclofenac is associated with a high incidence of phlebitis, thrombosis [116] and injection site reactions are common [117].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in case of an allergy, it is not possible to identify which of the individual drugs is responsible for the reaction. Although modest data exist to reduce the risk of physicochemical interactions between drugs [49], some studies have reported tolerability and efficacy with drug combinations (analgesics, anesthetics, muscle relaxants, etc.). More studies are needed to compare the combination with the single drug.…”
Section: Open Questions For the Next Clinical Researchmentioning
confidence: 99%
“…The current mesotherapeutic protocols suggest the administration of a single drug by local injection with needles of 27 Gauge × 4 mm and a low dose of the drug. It has also been recommended that the reflex effect produced by the needles has clinical benefits about pain 1,5,6…”
Section: Introductionmentioning
confidence: 99%